Explain-from-Stroke: Capturing Invisible Learning Processes Through Handwriting Dynamics Analysis - Nakamoto, Ryosuke; Flanagan, Brendan; Nakamura, Kohei; Ogata, Hiroaki (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Educational assessment requires understanding student problem-solving processes, not just final answers. Current AI-driven analytics focus on static outcomes, missing valuable insights from temporal dynamics. Explain-from-Stroke is a practical framework that captures invisible learning processes by integrating handwriting dynamics with vision-language models. The system extracts temporal features such as writing speed, pauses, and revisions, providing additional context for generating meaningful insights into hidden aspects of student reasoning. Using real classroom data from a Japanese secondary school, the model shows an 18.2% improvement in cognitive depth analysis compared with static approaches. This work provides educators with an accessible method to analyze learning processes using standard tablet technology.